2020
DOI: 10.1101/2020.03.28.013383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple and Robust Fabrication and Characterization of Conductive Carbonized Nanofibers Loaded with Gold Nanoparticles for Bone Tissue Engineering Applications

Abstract: Bone tissue engineering is a new and applicable emerging approach to repair the bone defects. In this regard, designing and robust fabrication of tissue engineering scaffolds that could provide an appropriate environment for cell proliferation and differentiation is of high interest.Electrical conductive scaffolds which provide a substrate for stimulating cell growth and differentiation through a physiologically relevant physical signaling, electrical stimulation, has shown a highly promise in this approach. I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…[ 43,44 ] It has been one of the earliest known cellulose derivatives utilized in many applications such as packaging films, gas separation, and water purification membranes. [ 45–48 ] It is characterized by a simple structure and excellent characteristics such as availability from diversity of resources, biodegradability, advantageous physical performance, simple processing, high transparency, and distinctive mechanical properties. [ 49,50 ] CA‐based nanocomposites exhibit high sensitivity and faster response times due to their high surface area and high porosity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43,44 ] It has been one of the earliest known cellulose derivatives utilized in many applications such as packaging films, gas separation, and water purification membranes. [ 45–48 ] It is characterized by a simple structure and excellent characteristics such as availability from diversity of resources, biodegradability, advantageous physical performance, simple processing, high transparency, and distinctive mechanical properties. [ 49,50 ] CA‐based nanocomposites exhibit high sensitivity and faster response times due to their high surface area and high porosity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant efforts have been put forward in the fabrication of conductive electrospun scaffold for effective bone tissue engineering. In this context, a representative study demonstrated the fabrication of electrospun carbon nanofibers functionalized with gold nanoparticle and evaluated their performance in the bone tissue engineering application [117]. The outcome confirmed that the developed electrospun conductive nanofibrous scaffold could be successfully employed in the bone tissue engineering application [117].…”
Section: Bone Tissue Engineeringmentioning
confidence: 72%
“…Various studies reported the positive effects of metallic NPs on bone regeneration. In our previous study [13] we showed that the incorporation of gold NPs enhanced the performance of CNFs. De Santis et al [14] fabricated a 3D-scaffold based on poly(ɛcaprolactone) (PCL) composited with iron-doped HAp (FeHAp) nanoparticles.…”
Section: Introductionmentioning
confidence: 92%